'I really like teaching, but…' understanding pre-service teachers' motivations and perceptions about teaching as a career choice. Issue 2 (15th March 2023) - Wang, Wenting; Wang, Ziyou; Lin, Wei
ABSTRACT: This study investigates pre-service teachers' motivations and perceptions about the decision to choose teaching as a career choice. Twenty-seven students who have embarked on teacher education programme in Scotland were interviewed. It was found that students conveyed ambivalent feelings and perspectives in the decision to teach in the sense that they perceived teaching as a platform to fulfil their career aspirations and enjoy themselves but also portrayed teaching negatively in relation to workload, work-related stress, salary, and social status. In light of expectancy-value theory, this study concludes that participants' seemingly highly intrinsically motivated to pursue a teaching career is likely to involve the feature of weighing the intrinsic rewards of teaching (enjoyment or fulfilment) and the negative perceptions deriving from a high level of workload and emotional stress and low salary and social status. The findings of this study have important practical implications for recruiting and retaining teachers; and, for helping future teachers fulfil their interests and articulated professional goals.